Investigation on Thermally Evaporated Aluminium Contact Layers for Perovskite Solar Cell Applications - Sia, Rachael, Wan Lyn; Low, Pei-Ling; Abdelrahman Hamed Ebrahem Abdelhamed; Thien, Gregory Soon How; Sin, Yew-Keong; Chan, Kah-Yoong (International Journal of Integrated Engineering, 2024)
Perovskite solar cells (PSCs) have gained wide interest due to their high device efficiency of up to 22.1%. Perovskite solar cells are comprised of five main layers: fluorine-doped tin oxide (FTO) glass, titanium dioxide (TiO2) electron transport layer (ETL), perovskite active layer, Spiro-OMeTAD hole transport layer (HTL), and a metal contact layer. The metal contact layer plays a significant role in collecting and transporting the generated current and hence governs the performance of the device. Aluminium (Al) is more cost-efficient than the commonly used silver (Ag) or gold (Au) contact layers in perovskite solar cells. The aim of this work is to investigate the influence of different thicknesses and surface morphologies on the electrical properties of the Al thin film contact layers for perovskite solar cell applications. The Al contact layers were deposited using a thermal evaporator with varying Al wire source lengths at constant deposition duration and pressure. The deposited films were characterised for thickness, morphology, and electrical properties using a stylus profilometer, an atomic force microscope, and a four-point probe, respectively. Results showed that thicker Al films have larger particle sizes as compared to the thinner films, demonstrating a more continuous film morphology. Resistivity and conductivity show a variance with different film thickness. Based on literature, higher conductivity and larger particle sizes of the metal contact layers can improve charge transportation, which contributes to the performance of the perovskite solar cell.